Community emergency medicine: taking the ED to the patient: a 12-month observational analysis of activity and impact of a physician response unit. Issue 9 (19th December 2019) - Joy, Tony; Ramage, Lisa; Mitchinson, Sophie; Kirby, Oliver; Greenhalgh, Rob; Goodsman, Danë; Davies, Gareth
Abstract : Background and objectives: International and national health policies advocate greater integration of emergency and community care. The Physician Response Unit (PRU) responds to 999 calls 'taking the Emergency Department to the patient'. Operational since 2001, the service was reconfigured in September 2017. This article presents service activity data and implications for the local health economy from the first year since remodelling. Methods: A retrospective descriptive analysis of a prospectively maintained database was undertaken. Data collected included dispatch information, diagnostics and treatments undertaken, diagnosis and disposition. Treating clinical teams recorded judgments whether patients managed in the community would have been (1) conveyed to an emergency department (ED)and (2) admitted to hospital, in the absence of the PRU. Hospital Episode Statistics data and NHS referencing costs were used to estimate the monetary value of PRU activity. Results: 1924 patients were attended, averaging 5.3 per day. 1289 (67.0%) patients were managed in the community. Based on the opinion of the treating team, 945 (73.3%) would otherwise have been conveyed to hospital, and 126 (9.7%) would subsequently have been admitted. The service was estimated to deliver a reduction of 868 inpatient bed days and generate a net economic benefit of £530 107. Conclusions: The PRU model provides community emergency medical care and early patient contact with a senior clinical decision-maker. It engages with community providers in order to manage 67.0% of patients in the community. We believe the PRU offers an effective model of community emergency medicine and helps to integrate local emergency and community providers.